An interpretation map: finding paths to reading processes - B. Green (Acta Theologica)
A consideration of the origins, development, and aftermath of Reader?Response theory helps place both possibilities and limits on the role of reading and interpretation of texts, biblical in particular. With its main tenets and representatives surveyed, it can be correlated with the historical?critical enterprise that it challenged and with the literary turn that preceded and paved the way for it. Finally, it offers us a context in which to place and appreciate pre?critical Jewish and Christian interpretations. The article closes with a set of suggestions for interpretation in view of its long history in biblical studies.